Historia Scholae Dvcalis Wolfenbvttelensis - Dommerich, Johann Christoph,Karl,Matthaei, Johann Gottlieb Anton (Typis Io. Theoph. Ant. Mattheen, 1750)
Wolfenbüttel, Große Schule, Einladungsschr. zur Geburtstagsfeier von Karl, Herzog von Braunschweig-Lüneburg, 1750
VD18 90721063